Dryland farming - Saxena, Jagdeep (Kurukshetra: A Journal of Rural Development)
Ryland farming is challenging with many constraints, but with the understanding of local climate and soil conditions, the selection of suitable crops, and the use of appropriate technologies, dryland farmers can farmers can grow multiple crops in single season with extra horticultural or livestock production. Reproduced